Policy Challenges for Campus Teaching Programs in Non-Educational Study Programs - Ambarwati, Arie; Pramudiana, Ika Devy (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The objective of this research is to identify and elucidate the obstacles encountered by non-educational study programmes in facilitating their students’ participation in the Kampus Mengajar programme, which constitutes one of the Merdeka Belajar Kampus Merdeka (MBKM) policy initiatives. This research employs a descriptive approach, utilising qualitative research methods. The research employed a variety of data collection techniques, including in-depth interviews, observation, and document analysis. The research findings indicate that there are two principal challenges: those of an administrative nature and those of a technical nature. The administrative challenge is that universities must align their implementation of the MBKM with their financial conditions and capabilities. The implementation of the Teaching Campus MBKM programme is hindered by two main challenges: a lack of funding, particularly from students, and an inadequate academic information system. Furthermore, there is a dearth of information regarding the technical implementation of the MBKM programme. The challenges described are not unique to this particular university; they are common to many other universities as well. These include funding, academic systems, quality, and productivity of human resources. Technical challenges in Kampus Mengajar programs include issues of communication competence in teaching, challenges of literacy skills, and the importance of a positive mental attitude in learning activities.